A new species of Orthomus Chaudoir, 1838 (Coleoptera: Carabidae) from Madeira island (Macaronesia) and notes on related species - Serrano, Artur R. M.; Aguiar, Carlos A. S.; Boieiro, Mário C.; Borges, Paulo A. V.; Rego, Carla; Arnorim, Isabel R.; Ribeiro, Sérvio P.; Pereira, Fernando (Zootaxa, 2009)
The present study describes a new ground-beetle species (Coleoptera, Carabidae) from Madeira island (type localities: FANAL and RIBEIRO BONITO), Orthomus (Nesorthomus) susanae Serrano & Borges, n. sp. Adults were sampled by means of pitfall traps. This work provides diagnostic characters, in particular the structure of male genitalia, and the distribution of this new species. Affinities to putative relatives and a key for the identification of males of the eight Orthomus (Nesorthomus) species of the Madeira island are also given.